Prognostic Significance of CD30 in Transformed Mycosis Fungoides: A Systematic Review and Meta-Analysis. Issue 3 (26th March 2021) - Travaglino, Antonio; Russo, Daniela; Varricchio, Silvia; Pignatiello, Sara; Baldo, Antonello; Picardi, Marco; Pane, Fabrizio; Mascolo, Massimo
Abstract: Objectives: Several studies suggested that CD30 expression is a favorable prognostic marker in transformed mycosis fungoides (tMF). However, evidence in this field is still unclear. This systematic review and meta-analysis aimed to evaluate the prognostic significance of CD30 in tMF. Methods: Electronic databases were searched from their inception to June 2020 for all studies assessing the prognostic value of CD30 in tMF. Pooled hazard ratio (HR) for death was calculated; a P value less than .05 was considered significant. Inconsistency index ( I 2 ) was used to assess statistical heterogeneity among studies. Results: Seven studies with 323 patients were included. CD30 expression in tMF was significantly associated with a decreased hazard of death both on univariate (HR, 0.459; 95% confidence interval [CI], 0.319-0.660; P < .001) and multivariate analysis (HR, 0.503; 95% CI, 0.345-0.734; P < .001), and the statistical heterogeneity among studies was null in all analyses ( I 2 = 0%). Conclusions: tMF cases with CD30 expression in large cells have a hazard of death two times lower than CD30-negative cases.